ОЛИЙ ТАЪЛИМ ТИЗИМИДА ЧЕТ ТИЛИ ДАРСЛАРИДА КАСБГА ЙУНАЛТИРИБ ЎҚИТИШНИНГ ҲОЗИРГИ ҲОЛАТИ - Тажиева, А.У.; Бекмуратова, Н.А. (SCIENCE and SOCIETY, 2021)
The article deals with the issues of content-based teaching at the lessons of foreign languages at the Higher Education system of Uzbekistan.